Abundance, diversity, and feeding behavior of coral reef buterflyfishes at Lord Howe Island - Pratchett, M.; Hoey, A.; Cvitanovic, C.; Hobbs, Jean-Paul; Fulton, C. (John Wiley & Sons, 2014)
Endemic species are assumed to have a high risk of extinction because their restricted geographic range is often associated with low abundance and high ecological specialization. This study examines the abundance of Chaetodon butterflyfishes at Lord Howe Island in the south-west Pacific, and compares interspecific differences in local abundance to the feeding behavior and geographic range of these species. Contrary to expected correlations between abundance and geographic range, the single most abundant species of butterflyfish was Chaetodon tricinctus, which is endemic to Lord Howe Island and adjacent reefs; densities of C. tricinctus (14.1 ± 2.1 SE fish per 200m2) were >3 times higher than the next most abundant butterflyfish (Chaetodon melannotus), and even more abundant than many other geographically widespread species. Dietary breadth for the five dominant butterflyfishes at Lord Howe Island was weakly and generally negative correlated with abundance.The endemic C. tricinctus was a distinct outlier in this relationship, though our extensive feeding observations suggest some issues with the measurements of dietary breadth for this species. Field observations revealed that all bites taken on benthic substrates by C. tricinctus were from scleractinian corals, but adults rarely, if ever, took bites from the benthos, suggesting that they may be feeding nocturnally and/or using mid-water prey, such as plankton. Alternatively, the energetic demands of C. tricinctus may be fundamentally different to other coral-feeding butterflyfishes. Neither dietary specialization nor geographic range accounts for interspecific variation in abundance of coral reef butterflyfishes at Lord Howe Island, while much more work on the foraging behavior and population dynamics of C. tricinctus will be required to understand its’ abundance at this location.